2000
DOI: 10.1590/s1516-89132000000200013
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal distribution of Hypostomus punctatus (Osteichthyes, Loricariidae) in a coastal stream from Rio de Janeiro, Southeastern Brazil

Abstract: Hypostomus punctatus was collected between June/1987 and July/1988, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
11
0
6
Order By: Relevance
“…A ocupação e distribuição de peixes ao longo de um Rio pode ser influenciada por fatores bióticos, como a temperatura, pH, salinidade, tipo de substrato, disponibilidade de alimento e estratégias reprodutivas (MENEZES & CARAMASCHI, 2000). De acordo com BARTHEM & GOULDING (1997) parece razoável crer, que a redistribuição de parte ou de toda a população no tempo e no espaço pode levar à combinação de algumas ou de todas as seguintes vantagens: aumento da taxa de crescimento, decréscimo da taxa de mortalidade e aumento da taxa de natalidade.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A ocupação e distribuição de peixes ao longo de um Rio pode ser influenciada por fatores bióticos, como a temperatura, pH, salinidade, tipo de substrato, disponibilidade de alimento e estratégias reprodutivas (MENEZES & CARAMASCHI, 2000). De acordo com BARTHEM & GOULDING (1997) parece razoável crer, que a redistribuição de parte ou de toda a população no tempo e no espaço pode levar à combinação de algumas ou de todas as seguintes vantagens: aumento da taxa de crescimento, decréscimo da taxa de mortalidade e aumento da taxa de natalidade.…”
Section: Discussionunclassified
“…Resultados semelhantes foram encontrados para Hypostomus punctatus (MENEZES & CARAMASCHI, 2000) e Astyanax janeiroensis (MAZZONI et al, 2004). Como no período de estudo, indivíduos maduros foram encontrados nos três pontos amostrais o deslocamento em direção às cabeceiras não parece estar relacionado, pelo menos não exclusivamente, com a desova.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Mazzoni and Iglesias-Rios (2002) found that canopy abundance determined the occurrence of M. microlepis while H. malabaricus densities were positively correlated to marginal vegetation and P. vivipara was correlated to the pools and clay substratum. Menezes and Caramaschi (1994; observed that the occurrence of juveniles of Hypostomus gr. punctatus was associated with marginal vegetation while adult individuals were found in rocky habitats and holes in the river banks.…”
Section: Discussionmentioning
confidence: 99%
“…Braga et al 2007) and spatial distribution (e.g. Aranha & Caramaschi 1997, Menezes & Caramaschi 2000, Mazzoni & Iglesias-Rios 2002b, Mazzoni et al 2004. Besides these studies, an important volume was published around ten years ago ) which included seminal papers regarding the origin and evolution of this ichthyofauna (Castro 1999), aspects of its historical biogeography (Buckup 1999), trophic structure (Esteves & Aranha 1999) and fish production (Mazzoni 1999), among others.…”
Section: Introductionmentioning
confidence: 99%